2016
DOI: 10.17344/acsi.2015.1340
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of High Performance Liquid Chromatography Method for Simultaneous Determination of Some Purine and Pyrimidine Bases

Abstract: Nine purine and pyrimidine bases were separated and determined simultaneously using reversed phase (RP) high performance liquid chromatography (HPLC) in some food samples and biological fluids. Chromatographic behavior of these ionizable compounds highly depends on the interactions with the solvent as confirmed experimentally and by calculation of distribution of this species as a function of pH. Chromatograms show the optimal separation of five purine (uric acid, hypoxanthine, xanthine, adenine, and guanosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Thus, development of a simple, rapid, and sensitive method for continual monitoring of its level in human body fluids including urine is vital. A range of techniques including chromatography [7, 8], electrophoresis [9, 10], potentiometry [11], spectroscopy [12], and amperometry [13] have been reported for determination of UA in different samples.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, development of a simple, rapid, and sensitive method for continual monitoring of its level in human body fluids including urine is vital. A range of techniques including chromatography [7, 8], electrophoresis [9, 10], potentiometry [11], spectroscopy [12], and amperometry [13] have been reported for determination of UA in different samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, significant inter-day variations in salivary levels of HX and XA (and UA) have been reported by Kochańska et al, which may explain the variations in HX and XA concentrations observed in this study. Markelj et al (Kochanska et al 2000;Markelj et al 2016) reported the analysis of saliva and urine by LC-MS, which showed that concentrations of HX and XA were significantly lower, relative to the concentration of UA, in saliva than in urine, although salivary UA has been shown to have a linear correlation with serum UA concentrations (Soukup et al 2012).…”
Section: Lc-faims-ms Determination Of Salivary Hypoxanthine and Xanthmentioning
confidence: 99%
“…HX and XA have been detected in plasma, serum or urine using a variety of methods including high performance liquid chromatography (HPLC) and capillary electrophoresis (Guan et al 2004(Guan et al , 2005Markelj et al 2016). These oxypurines have also been detected in saliva (Al-Shehri et al 2013;Guan et al 2004Guan et al , 2005Kochanska et al 2000;Markelj et al 2016), which is known to change in response to a variety of different physiological states (Dame et al 2015). However, saliva is a complex biofluid which can require careful sample preparation and/or extended analysis times to separate HX and XA from co-eluting matrix interferences.…”
Section: Introductionmentioning
confidence: 99%
“…Carboxylic-MWCNTs have been used in CZE and have shown promising achiral separations of purine and pyrimidine bases. Liquid chromatography has been widely used for the separation of pyrimidine and purine bases due to its high sensitivity, selectivity and reproducibility [ 158 , 159 , 160 ]. Capillary electrophoresis also showed promising separation behaviour for the polar and even not fully ionized compounds including pyrimidine and purine bases [ 161 , 162 ].…”
Section: Mwcnts For Achiral Separation In Biologicsmentioning
confidence: 99%